Research note: Chicken seminal plasma metabolome and fertility-enhancing effects of l-carnitine supplementation in semen - Yunlei Li; Lijun Jiang; Yunhe Zong; Aixin Ni; Xintong Han; Adamu Mani Isa; Jingwei Yuan; Jilan Chen; Yanyan Sun (Poultry Science)
Sperm motility is crucial for poultry reproductive efficiency. Seminal plasma is an essential component of semen, and its constituents are linked to sperm motility. This study investigated metabolomics in chicken seminal plasma associated with sperm motility and explored the fertility-enhancing potential of l-carnitine. Semen samples were collected from 16 individual chickens, including 8 with high sperm motility and 8 with low sperm motility. Each sample was divided into two portions: fresh or incubated at 37°C for 30 minutes. A total of 32 seminal plasma samples were obtained and investigated using a nontargeted metabolomics approach. Results indicated that the differential metabolites could be categorized into carnitine-related compounds, choline-related phospholipids, nucleotide derivatives, amino acid-related metabolites and other lipid mediators. More abundance of choline-related, nucleotide derivatives, and lipid mediators in low sperm motility group and incubated groups were identified. A significant decrease in the short-chain acylcarnitine 2-methylbutyroylcarnitine was associated with low sperm motility. Meanwhile, medium- and long-chain acyl-carnitines were elevated in incubated seminal plasma compared to fresh samples. Since acyl-carnitines are formed from carnitine and fatty acids, the potential function of l-carnitine in semen was further determined. An artificial insemination was performed using semen samples either fresh or incubated, and with or without additional of l-carnitine. After in-vitro incubation, samples supplemented with l-carnitine showed significantly improved sperm fertilizing capacity than the unsupplemented group. In conclusion, this study concluded that carnitine compounds play a crucial role in sperm motility, and l-carnitine supplementation enhanced sperm fertility and prolong sperm viability during in vitro storage. These findings suggest potential benefits for both rooster breeding and artificial insemination practices.